Analisis Kepuasan Pelanggan Terhadap Bauran Pemasaran Jasa Suatu Studi di SD Kartini 1 Batam - Rusda Irawati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
Among many research conducted related to customer satisfaction, this research aims to analyzed the customer satisfaction related to implementation service marketing mix in privat elementary school Kartini 1 Batam. A questionnaire given to 264 student parents and who returned are 147 a questionnaire. Overall average customer satisfaction SD Kartini 1 is very high, with the score according to criteria 81-100. Variable with very high satisfaction index is product/service (0.88), promotion (0.87), distribution (0.83), process (0.84) and personnel (0.84). The rest is variable satisfaction high index with score 61-80, are physical evidence (0.76) and price (0.78)